2012
DOI: 10.1371/journal.pone.0035553
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Combination of Male Germ Cell miRNAs Coordinates Gonocyte Differentiation

Abstract: The last 100 years have seen a concerning decline in male reproductive health associated with decreased sperm production, sperm function and male fertility. Concomitantly, the incidence of defects in reproductive development, such as undescended testes, hypospadias and testicular cancer has increased. Indeed testicular cancer is now recognised as the most common malignancy in young men. Such cancers develop from the pre-invasive lesion Carcinoma in Situ (CIS), a dysfunctional precursor germ cell or gonocyte wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 75 publications
4
46
1
1
Order By: Relevance
“…Although studies on testicular miRNAs are limited, it is known that there are miRNAs preferentially or specifically expressed within the testis (McIver et al 2012). Using miRNA microarray analysis of isolated gonocytes and spermatogonia from mice, the authors identified miRNAs that were differentially expressed between gonocytes and spermatogonia.…”
Section: R142 G Manku and M Cultymentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies on testicular miRNAs are limited, it is known that there are miRNAs preferentially or specifically expressed within the testis (McIver et al 2012). Using miRNA microarray analysis of isolated gonocytes and spermatogonia from mice, the authors identified miRNAs that were differentially expressed between gonocytes and spermatogonia.…”
Section: R142 G Manku and M Cultymentioning
confidence: 99%
“…Of those pathways, it was the PTEN and Wnt/b-catenin signaling pathways that were associated with the majority of miRNAs, pinpointing to the cell cycle regulator cyclin D1 as a common target of both pathways. Given the known role of Cyclin D1 in promoting cell progression to S phase, the authors proposed that the observed miRNA changes between gonocyte and spermatogonia might be related to their role in gonocyte differentiation (McIver et al 2012). However, exactly what role these signaling pathways are playing in gonocyte differentiation remains yet to be determined.…”
Section: R142 G Manku and M Cultymentioning
confidence: 99%
“…Novotny and coworkers conclude from these results that the miRNA expression profile changes during testis development and that the miRNA profile of adult testis with GCNIS cells shares characteristic similarities with the expression in fetal gonocytes (Novotny et al 2012). McIver and coworkers screened for changes in miRNA expression between postnatal gonocytes and spermatogonia to gain insight into the miRNA processes that influence maturation of gonocytes and might cause GCNIS development (McIver et al 2012). They found seven differentially expressed miRNAs (upregulated in spermatogonia vs gonocytes: miR136, -743q and -463; downregulated miR290-5p, -291a-5p, -293 and -294) that are involved in regulation of PTEN and WNT signaling and CyclinD1 (McIver et al 2012).…”
Section: Screening For Gc-and Gct-specific Expression Of Noncoding Rnasmentioning
confidence: 99%
“…McIver and coworkers screened for changes in miRNA expression between postnatal gonocytes and spermatogonia to gain insight into the miRNA processes that influence maturation of gonocytes and might cause GCNIS development (McIver et al 2012). They found seven differentially expressed miRNAs (upregulated in spermatogonia vs gonocytes: miR136, -743q and -463; downregulated miR290-5p, -291a-5p, -293 and -294) that are involved in regulation of PTEN and WNT signaling and CyclinD1 (McIver et al 2012). The miRNA cluster 290-295 is highly expressed in ESCs and promotes proliferation and pluripotency by maintaining OCT3/4 expression (Zheng et al 2011).…”
Section: Screening For Gc-and Gct-specific Expression Of Noncoding Rnasmentioning
confidence: 99%
See 1 more Smart Citation